Pembrolizumab in advanced soft-tissue sarcoma and bone sarcoma (SARC028): a multicentre, two-cohort, single-arm, open-label, phase 2 trial. Issue 11 (November 2017) - Tawbi, Hussein A; Burgess, Melissa; Bolejack, Vanessa; Van Tine, Brian A; Schuetze, Scott M; Hu, James; D'Angelo, Sandra; Attia, Steven; Riedel, Richard F; Priebat, Dennis A; Movva, Sujana; Davis, Lara E; et al.
Summary: Background: Patients with advanced sarcomas have a poor prognosis and few treatment options that improve overall survival. Chemotherapy and targeted therapies offer short-lived disease control. We assessed pembrolizumab, an anti-PD-1 antibody, for safety and activity in patients with advanced soft-tissue sarcoma or bone sarcoma. Methods: In this two-cohort, single-arm, open-label, phase 2 study, we enrolled patients with soft-tissue sarcoma or bone sarcoma from 12 academic centres in the USA that were members of the Sarcoma Alliance for Research through Collaboration (SARC). Patients with soft-tissue sarcoma had to be aged 18 years or older to enrol; patients with bone sarcoma could enrol if they were aged 12 years or older. Patients had histological evidence of metastatic or surgically unresectable locally advanced sarcoma, had received up to three previous lines of systemic anticancer therapy, had at least one measurable lesion according to the Response Evaluation Criteria In Solid Tumors version 1.1, and had at least one lesion accessible for biopsy. All patients were treated with 200 mg intravenous pembrolizumab every 3 weeks. The primary endpoint was investigator-assessed objective response. Patients who received at least one dose of pembrolizumab were included in the safety analysis and patients who progressed or reached at least one scan assessment were included in the activity analysis. Accrual is ongoing in some disease cohorts. This trial is registered with ClinicalTrials.gov, number NCT02301039 . Findings: Between March 13, 2015, and Feb 18, 2016, we enrolled 86 patients, 84 of whom received pembrolizumab (42 in each disease cohort) and 80 of whom were evaluable for response (40 in each disease cohort). Median follow-up was 17·8 months (IQR 12·3–19·3). Seven (18%) of 40 patients with soft-tissue sarcoma had an objective response, including four (40%) of ten patients with undifferentiated pleomorphic sarcoma, two (20%) of ten patients with liposarcoma, and one (10%) of ten patients with synovial sarcoma. No patients with leiomyosarcoma (n=10) had an objective response. Two (5%) of 40 patients with bone sarcoma had an objective response, including one (5%) of 22 patients with osteosarcoma and one (20%) of five patients with chondrosarcoma. None of the 13 patients with Ewing's sarcoma had an objective response. The most frequent grade 3 or worse adverse events were anaemia (six [14%]), decreased lymphocyte count (five [12%]), prolonged activated partial thromboplastin time (four [10%]), and decreased platelet count (three [7%]) in the bone sarcoma group, and anaemia, decreased lymphocyte count, and prolonged activated partial thromboplastin time in the soft-tissue sarcoma group (three [7%] each). Nine (11%) patients (five [12%] in the bone sarcoma group and four [10%] in the soft-tissue sarcoma group) had treatment-emergent serious adverse events (SAEs), five of whom had immune-related SAEs, including two with adrenal insufficiency, two with pneumonitis, and one with nephritis. Interpretation: The primary endpoint of overall response was not met for either cohort. However, pembrolizumab showed encouraging activity in patients with undifferentiated pleomorphic sarcoma or dedifferentiated liposarcoma. Enrolment to expanded cohorts of those subtypes is ongoing to confirm and characterise the activity of pembrolizumab. Funding: Merck, SARC, Sarcoma Foundation of America, QuadW Foundation, Pittsburgh Cure Sarcoma, and Ewan McGregor.